(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
The criminal justice system provides remedies for offences, as defined by the law of the land. So far as “offences against human” in India are concerned, the erstwhile Indian Penal Code (IPC), Criminal Procedure Code (CrPC), and Indian Evidence Act (IEA)were major laws that witnessed many amendments. The BHARATIYA NYAYA SANHITA, 2023 (BNS) completely repealed the former IPC last year. Criminal investigation agencies rely mainly on examination of a person- living or dead–as the case may be and subsequently report of such examination by the Registered Medical Practitioner (RMP) / board of experts form a critical base for further investigations and legal recourse. Once the case is committed for trial, the opinion of RMP and analysis reports of various samples collected are also of immense importance for the prosecution side. The medicolegal opinion by RMP is based on one’s personal knowledge of “Forensic Medicine & Toxicology” coupled with practical exposure to such cases. The recent biomedical and legal literature permits one to conclude that the evidential interpretation of such opinion/s is more legal than that based on medical science. With due respect to all concerned stakeholders of the Criminal Justice Delivery System”, an attempt has been made to review the present scenario and contemplate solutions, if desired.